Hearing loss and acquired immune deficiency syndrome: systematic review - Araújo,Eliene da Silva (2012)
PURPOSE: To investigate the occurrence of hearing loss in individuals with HIV/AIDS and their characterization regarding type and degree. RESEARCH STRATEGY: It was conducted a systematic review of the literature found on the electronic databases PubMed, EMBASE, ADOLEC, IBECS, Web of Science, Scopus, Lilacs and SciELO. SELECTION CRITERIA: The search strategy was directed by a specific question: "Is hearing loss part of the framework of HIV/AIDS manifestations?", and the selection criteria of the studies involved coherence with the proposed theme, evidence levels 1, 2 or 3, and language (Portuguese, English and Spanish). DATA ANALYSIS: We found 698 studies. After an analysis of the title and abstract, 91 were selected for full reading. Out of these, 38 met the proposed criteria and were included on the review. RESULTS: The studies reported presence of conductive, sensorineural, and mixed hearing loss, of variable degrees and audiometric configurations, in addition to tinnitus and vestibular disorders. The etiology can be attributed to opportunistic infections, ototoxic drugs or to the action of virus itself. The auditory evoked potentials have been used as markers of neurological alterations, even in patients with normal hearing. CONCLUSION: HIV/AIDS patients may present hearing loss. Thus, programs for prevention and treatment of AIDS must involve actions aimed at auditory health.